1966
DOI: 10.1121/1.2143496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plane-Symmetric Mass Loading on the Response of Ring-Stiffened Cylindrical Shells

Abstract: An analytical study of the in vacuo vibrations of a simply supported, mass-loaded thin cylindrical shell that is reinforced by equally spaced ring stiffeners is presented. Four masses are attached to each stiffening ring in a plane-symmetric fashion. The rotatory inertia of the masses is taken into account, but similar effects for the shell and ring stiffeners are neglected. Lagrange's equations are used to derive the dynamic equations of the shell structure and the Jacobi iteration method is employed to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1975
1975

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Suitable solutions to equations (6) and ( Substituting (8) and (9) into (6) and (7), it is found that equation (6) is identically satisfied, whereas equation (7) will be …”
Section: B Solution Of the Governing Equationsmentioning
confidence: 99%
“…Suitable solutions to equations (6) and ( Substituting (8) and (9) into (6) and (7), it is found that equation (6) is identically satisfied, whereas equation (7) will be …”
Section: B Solution Of the Governing Equationsmentioning
confidence: 99%